Effect of cryogenic rolling on the microstructural characteristics and mechanical properties of Custom 465 stainless steel: Suppression of austenite reversion transformation during ageing treatment - Chih-Yuan Chen; Yu-Shan Chang (Journal of Materials Research and Technology, 2025)
Although the positive effects of cryogenic rolling (CR) before ageing have been demonstrated in several fcc/hcp crystals, the influence of CR on maraging stainless steel (bcc) has not been completely investigated yet. Therefore, samples of Custom 465 stainless steel were treated with different levels (35 % and 70 %) of cryogenic rolling strain (CRS), followed by ageing at low (520 °C) and high (640 °C) temperatures for different times. Surprisingly, irrespective of the amount of CRS, it was found that the reverted austenite could form only when the ageing was performed at 640 °C, and no significant austenite reversion occurred at 520 °C, which implies suppression of the austenite reversion transformation and thus profoundly impacts the mechanical properties. For instance, according to measurements obtained via the SEM-EBSD technique, the fractions of reverted austenite in steel samples subjected to 70 % CRS were 0.1 % after ageing at 520 °C for 1 h and 13.3 % after ageing at 640 °C for 1 h, respectively. In addition, as expected, it was also found that the strength increased with CRS. On the other hand, the amount of reverted austenite decreased with isothermal ageing time, indicating poor thermal stability of the reverted austenite. Furthermore, regardless of ageing condition, the traditional trade-off between strength and ductility was confirmed for the Custom 465 stainless steel with increasing CRS.